Understanding how pre-impact posture can affect injury outcome in side impact sled tests using a new tool for visualization of cadaver kinematics. Issue 3 (5th February 2015) - Donlon, John Paul; Poulard, David; Lessley, David; Riley, Patrick; Subit, Damien
Abstract The effect of posture and subject-specific factors on injury outcome is an active field of research in injury biomechanics, in particular in automotive safety research where post-mortem human subjects (PMHS) are used as surrogates. Current PMHS tests routinely include acquisition of the subjects׳ geometry and kinematics. However, combining these two datasets to better understand the injury mechanism is still a challenge. This study investigated the connection between pre-impact posture and resulting injuries in six previously published side impact sled tests (three with a rigid wall and three with an airbag) by creating three-dimensional kinematic animations (3DKA) of the tests. The 3DKA allow qualitative assessment of parameters related to posture and their possible effect on injury outcome. The orientation of the struck scapula and the lateral leaning of the torso were identified as potentially significant parameters. The ranges of variation in these parameters were quantified and compared to the number of rib fractures for each subject: the data suggested a correlation, but there was insufficient data for a probabilistic analysis. The 3DKA were published with this study and are freely available.